Sustainable Cities Authenticity, Ambition and Dream - Almusaed, Amjad; Almssad, Asaad (IntechOpen, 2019)
This book has been written to represent the efficient applications of sustainability in urban areas. The book intends to illustrate various techniques of action on sustainability on city conception, functions and conformation. This book is divided into four parts and nine chapters: Section I is entitled "Introduction to Sustainable Cities Concept" and contains one chapter "Introductory chapter: Overview of Sustainable Cities Theory and Practices," which discusses sustainability in cities in conception and practice. Section II is entitled "Energy and Environmental Analysis of Sustainable Cities Models." This includes four chapters. It expresses the effect of the environment and energy embodiment on city configuration and function. Section III is entitled "The Role of Transport in a Sustainable City." This part includes two chapters. Section IV is entitled "The influence of Social and Economic Factors in Urban Space Conception." It includes two chapters.